THE EUROPEAN DIMENSION OF THE COMPETENCE-BASED SCHOOL EDUCATION IN UKRAINE - Olena LOKSHYNA (National Centre for Policy and Evaluation in Education, 2018)
The adoption of the Lisbon Strategy (2000) and of the European Reference Framework on Key Competences for Lifelong Learning (2006) launched a competence-based approach in the EU member states education systems. During the last decade the concept of competence greatly influenced the education policy, school curricula and assessment models. The competence approach serves as an Europeanisation tool harmonising the education systems in order to raise their quality and, thus, to make the EU economy competent in the world. The Ukrainian education is under great influence of pan-European tendencies and policies that results in its Europeanisation. The competence approach is one of the tools of this process at the level of school education. Ukraine has travelled long pass from the discussion and definition of competences to the selection and adoption at the nationwide level. Still, this process is accompanied by a number of challenges that make the European experiences significant for the Ukrainian education in the process of its integration into the European education space.